Enablers and Barriers of Antenatal Health Utilization among Pregnant Women in India: A Comparative Scrutiny from NFHS-4 & 5 - Kesarwani, Priyanka; Tripathi, Akhilesh Kumar; Kumar, Arunesh; Bihari, Anand; Srivastava, Ankit (Indian Journal of Community Health, 2024)
Background: The use of effective antenatal care (ANC) plays a important role for minimizing maternal and child mortality and morbidity. Antenatal care (ANC) is the use of suitable and successful screening, preventive, or treatment interventions to minimize the risk of unfavorable health outcomes for mother and child during pregnancy and childbirth. Aims & Objectives: This study assesses the dynamic nature of various predictors associated with optimal ANC utilization in India. Methodology: A secondary data analysis was done based on NFHS-4 & NFHS-5. A uniform sample design, which is representative at the national, state/union territory and district level, is adopted in each round of the survey. Each district is stratified into urban and rural areas. Effect size with a p-value <0.05 were declared as significant factors associated with ANC utilization in both NFHS-4 & 5. This study is based on secondary data so not required IEC approval. Results: ?4 ANC visits by women during pregnancy increases from around 51% to 58% from NFHS-4 to NFHS-5. However, higher household wealth status, women with higher education and exposure to the media were coming out to be enablers while women with higher birth order, women belonging rural setup, distance to health facility coming out to be significant barriers in both the rounds of NFHS for the recommended ANC (?4) visit through with varying effect sizes. Conclusion: According to our research, sociodemographic and health policy interventions, such as enhancements to social services and education, as well as community health education, particularly for women living in rural areas, can reduce obstacles to the advised use of ANC services in India.